Risk Factors of Dental Cavities in Children - Elsa Luján Hernández; Marta Luján Hernández; Nora Sexto Delgado (Medisur)
Background: Dental cavities are a kind of disease that is increasing. The quantitative change has also produced qualitative changes concerning the type, extension and location of the lesions. Objective: To identify the selected risks of dental cavities among the students of a primary school. Methods: An analytic investigation of the controls and cases performed during academic course 2004 to 2005. The universe was constituted by 320 students where 204 were selected for this study. The cases were selected among the children who were affected by cavities (102) and the controls were selected by a simple randomized sample, i.e. a control one for each case (102). A consultation was carried out in the school to value the risks and the presence of the disease. Affectation due to cavities, malocclusion, and parodontopathies, age, sex, scholar degree, bad oral hygiene, previous experience of cavities in primary and permanent dentition, saliva viscosity, dental overlapping, orthodontic treatment, and sugar candies ingestions were the variables analyzed. Results: It was corroborated that the 49.5 % of the cases were affected by cavities, 23 % by malocclusion, and parodontopathies were observed in the 2, 0 %. The 80.3 % of the cases had a very bad oral hygiene, 50 % presented saliva viscosity and 95.1 % of the cases used to ingest sugar candies. Conclusions: The association between the classic risks of dental cavities appearance such as bad oral hygiene, previous experience of cavities, saliva viscosity and sugar candies ingestion were shown in this study.